Strengthening legal frameworks for vaccination: The experiences of Armenia, Georgia, and Moldova. Issue 35 (14th August 2019) - Trumbo, Silas P.; Silver, Dana; Domenti, Oxana; Gasoyan, Hamlet; Paatashvili, Eka; Gellin, Bruce G.; Gordon, Jennifer L.
Highlights: Details middle-income countries' efforts to strengthen legal frameworks for immunization. Legislation can promote country ownership of immunization systems. A better understanding of the impact of frameworks on sustainable immunization is needed. Abstract: Background: Gavi, the Vaccine Alliance, delivers life-saving vaccines to children in the world's poorest countries and encourages countries to assume increasing ownership of their immunization programs as their economies grow. Vaccination legislation may promote country ownership and immunization program sustainability. However, despite establishment of vaccination laws as an indicator of national commitment to immunization through the Global Vaccine Action Plan, little is known about the content of vaccination legislation in low- and middle-income countries and the processes by which countries strengthen their legal frameworks. We describe the experiences of three countries supported by Gavi through its partnership with the Sabin Vaccine Institute— Armenia, Georgia, and Moldova—in strengthening their legal frameworks for vaccination as they transition from Gavi support. Methods: Information presented comes from national legal documents and the 2017 European Regional Workshop on Immunization Legislation, in which legislators and health officials from Armenia, Georgia, and Moldova shared approaches to making immunization a national priority by strengthening legal frameworks. We outline each country's legislative framework, describe progress in modifying vaccination legislation, and present strategies developed by countries to continue strengthening the legal basis of their immunization programs. Results: Armenia, Georgia, and Moldova have legal frameworks that guarantee immunization as a public good, define immunization calendars, and establish regulations for vaccine procurement and administration. Legislative priorities include modifications of regulations to optimize procurement (Armenia and Moldova), potential provisions to increase vaccination through incentives (Georgia) or requirements (Moldova, possibly Armenia), and new mechanisms to finance routine program costs (all three countries). Each country is employing a distinct approach to strengthen its legal framework. Conclusion: These country experiences suggest that while legal approaches can promote country ownership, there is no standardized approach to vaccination legislation. A better understanding of the complex legal frameworks and their impact on supporting and sustaining progress in vaccination is needed.